2015
DOI: 10.1165/rcmb.2013-0491oc
|View full text |Cite
|
Sign up to set email alerts
|

Early Exposure to Hyperoxia or Hypoxia Adversely Impacts Cardiopulmonary Development

Abstract: Preterm infants are at high risk for long-term abnormalities in cardiopulmonary function. Our objectives were to determine the long-term effects of hypoxia or hyperoxia on cardiopulmonary development and function in an immature animal model. Newborn C57BL/6 mice were exposed to air, hypoxia (12% oxygen), or hyperoxia (85% oxygen) from Postnatal Day 2-14, and then returned to air for 10 weeks (n = 2 litters per condition; > 10/group). Echocardiography, blood pressure, lung function, and lung development were ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
49
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 39 publications
7
49
0
Order By: Relevance
“…These could predispose the neonates with BPD to the development of respiratory illnesses later in their life. Similar persistent findings into adulthood have been found in neonatal mice exposed to hyperoxia (4,5,34,38,48).…”
supporting
confidence: 82%
See 1 more Smart Citation
“…These could predispose the neonates with BPD to the development of respiratory illnesses later in their life. Similar persistent findings into adulthood have been found in neonatal mice exposed to hyperoxia (4,5,34,38,48).…”
supporting
confidence: 82%
“…These could predispose the neonates with BPD to the development of respiratory illnesses later in their life. Similar persistent findings into adulthood have been found in neonatal mice exposed to hyperoxia (4,5,34,38,48).Several investigators have noted the protective effects of DHA and its downstream metabolites in various lung diseases. Levels of DHA decrease in premature neonates after birth (24), and this could potentially exacerbate the adverse effects of infection, inflammation, or oxidative stress.…”
supporting
confidence: 75%
“…Some studies suggested that hyperoxia increased compliance as in the case of emphysematous lungs, whereas other studies concluded hyperoxia decreased compliance because the lungs are less pliable (47)(48)(49)(50). We tested murine pulmonary outcomes at 6 weeks in accordance with previous studies (36,47,49).…”
Section: Discussionmentioning
confidence: 98%
“…In BPD, hyperoxia-induced inflammation has also been linked to impaired lung biophysical properties, but with conflicting results; both increasing and decreasing compliance have been described (47)(48)(49). Some studies suggested that hyperoxia increased compliance as in the case of emphysematous lungs, whereas other studies concluded hyperoxia decreased compliance because the lungs are less pliable (47)(48)(49)(50).…”
Section: Discussionmentioning
confidence: 99%
“…Oxygen exposure in the neonatal period has been demonstrated to affect lungs of mice by increasing airway reactivity and persistent inflammation with alteration in the innate immunoregulatory pathways that contribute to “poorer resistance” to respiratory viral infections in adulthood (61, 62). Furthermore, the exposure of newborn mice to hyperoxia may lead to long-term cardiac abnormalities, such as left ventricular dysfunctions (63), and neurodevelopmental impairments in adult life, as demonstrated by abnormal behavior, deficits in spatial and recognition memory, small hippocampal dimensions, in the absence of intracranial pathology such as intraventricular hemorrhage or periventricular leukomalacia in the neonatal period (64). …”
Section: Oxygen Toxicitymentioning
confidence: 99%